Complex regional pain syndrome what is the outcome? ‐ a systematic review of the course and impact of CRPS at 12 months from symptom onset and beyond. (4th May 2022) - Johnson, Selina; Cowell, Fiona; Gillespie, Sharon; Goebel, Andreas
Abstract: Background and Objective: To improve CRPS treatment, it is imperative to understand the nature, degree and relative importance of ongoing problems associated with CRPS. The objective of this systematic review was to summarize the published data concerning measures of function and impact including occupational parameters, of CRPS at 12 months from symptom onset and beyond. Databases and Data Treatment: MEDLINE, EmBase and PsychINFO were searched (inception to May 2021). Study cohorts were eligible if they included; adult patients with the primary complaint of CRPS ≥12 months duration, outcomes that reported change in CRPS signs and symptoms, and physical and social function. Prospero registration: CRD42021241785. Results: Twenty‐two included studies suggest that pain and motor dysfunction are the most dominant long‐term features of CRPS, persisting for 51%–89% of patients at ≥12 months. On average for all patients who had CRPS at baseline, grip strength was found to be reduced by 25%–66%, and range of motion reduced by 20%–25% at ≥12 months. Such losses were associated with physical and social disability. Thirty to forty percent of all patients did not return to work and a further 27%–35% of persons returned to work but required some form of workplace adaptation, although the quality of this data was poor. Quality assessment highlighted limitations in the literature, such as high attrition bias and variations in diagnostic criteria. Conclusions: Results provide first‐time quantitative data including specific evidence about losses to motor function and long‐term compromises to work status. Results demonstrate that the ongoing impact of one episode of CRPS on limb function and work status is relatively high. Significance: This review provides first‐time clarity in relation to outcomes of limb function and work status associated with an episode of CRPS, beyond 12 months from onset. Results demonstrate that the long‐term impact of an episode of CRPS on these outcomes is much larger than previously described, and thus also illustrates how the wider health economic impact of CRPS is not yet fully understood. We additionally highlight the need for future research that identifies long‐term predictors, and treatments that can foster good functional and occupational recovery.